Perpaduan Ummah Membawa Kejayaan - Safei, Su'aidi (Terengganu Foundation Printing, 1999)
The intention to foster ties of solidarity and to forge closer unity requires an appreciation of the characteristics and spirit of hijrah nabawiyyah: i. The spirit of sacrifice of property and soul under the enemy crush, ii. The spirit of inculcating a sense of compassion and brotherhood, iii. The spirit of cooperation and collaboration.